The anguish of surrender : Japanese POW's of World War II - Straus, Ulrich (Donald R. Ellegood International Publications., 2003)
"On December 6, 1941, Ensign Kazuo Sakamaki was one of a handful of men selected to skipper midget subs on a suicide mission to breach Pearl Harbor's defenses. When his equipment malfunctioned, he couldn't find the entrance to the harbor. He hit several reefs, splitting the sub, and swam to shore some miles from Pearl Harbor. In the early dawn of December 8, he was picked up on the beach by two Japanese American MPs on patrol. Sakamaki became Prisoner No. 1 of the Pacific War."